Perilaku Pencegahan COVID-19 Pre dan Pasca Vaksinasi RSUP H. Adam Malik Medan - Simanjuntak, Novita Hasiani (Nommensen Journal of Medicine, 2023)
Background: Subramanian stated, countries with vaccination coverage of 75% of the population have a higher increase in COVID-19 cases compared to countries with vaccination coverage of 10% of the population. Prevention of COVID-19 is not enough just by vaccination, the 5M health protocol should still be carried out.Objective: The purpose of this study was to determine the relationship between COVID-19 prevention behavior (5M) before and after vaccination with COVID-19 vaccination in the community at H. Adam Malik General Hospital Medan. In addition to 5M's behavior, the frequency of AEFI COVID-19 was also seen.Methods: This is a cross sectional study with a survey approach. This research was conducted at the H. Adam Malik General Hospital Medan. The population is people 18 years and over who have not and have had 1st and 2nd vaccinations for COVID-19. Consecutive sampling techniques were used, as many as 200 people. Measuring with a questionnaire, 3 times, namely pre-1st vaccination, pre-2nd vaccination, and post-2nd vaccination. Non-parametric comparative analysis using the Friedman test, and Post Hoc analysis on mask wearing behavior.Results: Significant differences were found between the behavior of wearing masks pre1stvaccination nd pre2nd vaccination with p 0.008. The results of the analysis with the Friedman test on the behavior of wearing masks showed a significant relation, with p value 0.016. The most common AEFI COVID-19 that respondents complained about was muscle pain, as many as 81 people (40.5%).Conclusion: The trend shown is the increase in non-compliant behavior in carrying out 5M behavior, in each measurement.